Combining NanoKnife with M1 oncolytic virus enhances anticancer activity in pancreatic cancer. (1st April 2021) - Sun, Shuxin; Liu, Yang; He, Chaobin; Hu, Wanming; Liu, Wenfeng; Huang, Xin; Wu, Jiali; Xie, Fengxiao; Chen, Chen; Wang, Jun; Lin, Yuan; Zhu, Wenbo; et al.
Abstract: NanoKnife, a nonthermal ablation technique also termed irreversible electroporation (IRE), has been adopted in locally advanced pancreatic cancer (LAPC) treatment. However, reversible electroporation (RE) caused by heterogeneous electric field magnitude leads to inadequate ablation and tumor recurrence. Alphavirus M1 has been identified as a novel natural oncolytic virus which is nonpathogenic and with high tumor selectivity. This study evaluated improvements to therapeutic efficacy through combination therapy incorporating NanoKnife and M1 virus. We showed that IRE triggered reactive oxygen species (ROS)-dependent apoptosis in pancreatic cancer cells (PCCs) mediated by phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) pathway suppression. When NanoKnife was combined with M1 virus, the therapeutic efficacy was synergistically enhanced. The combinatorial treatment further inhibited tumor proliferation and prolonged the survival of orthotopic pancreatic cancer (PC)-bearing immunocompetent mice. In depth, NanoKnife enhanced the oncolytic effect of M1 by promoting its infection. The combination turned immune-silent tumors into immune-inflamed tumors characterized by T cell activation. Clinicopathologic analysis of specific M1 oncolytic biomarkers indicated the potential of the combination regimen. The combinatorial therapy represents a promising therapeutic efficacy and may ultimately improve the prognosis of patients with LAPC. Graphical abstract: Image 1 Highlights: Nanoknife induces ROS-dependent apoptosis in pancreatic cancer cells. M1 oncolytic virus synergizes with NanoKnife to alleviate pancreatic cancer. NanoKnife enhances M1 virus infection through electroporation. Combined therapy activates anti-tumor T cells in pancreatic cancer.